Development of Islamic Education (PAI) Curriculum based on Anti-Corruption Fiqh - Misno, Abd; Lur Rochman, Kholil; Idi, Abdullah; Maharani, Dewi; Hanna, (International Journal of Psychosocial Rehabilitation, 2020)
Corruption is an extraordinary crime that has resulted in losses for the country and society. In Indonesia, the crime of corruption has reached alarming limits. This is proven by the facts and data that state that Indonesia is ranked among the most corrupt countries in the world. Seeing this phenomenon, cursive and preventive actions are needed in order to prevent regeneration of these actions. The chairperson's action can be carried out by giving the heaviest laws to the perpetrators of the crime of corruption. While preventive action can be done by providing education and understanding of the crime of corruption.This study aims to develop a PAI curriculum based on anti-corruption fiqh. It starts by presenting an anti-corruption education model in Islamic religious education and anti-corruption fiqh content in Islamic religious education subjects. Curriculum development referred to in this study is an effort to integrate anti-corruption fiqh with PAI subjects. The form is in the form of an expansion of themes that already exist in the curriculum by using a contextual approach to the learning of anti-corruption fiqh, namely with the model of integrative-inclusive anti-corruption education in Islamic Religious Education. The integrative-inclusive AntiCorruption Education Model in Islamic religious education is applicable more as an approach in contextual-based learning.